Clinical Characterization of Ulcerative Colitis in Patients with Primary Sclerosing Cholangitis - Shun Murasugi; Ayumi Ito; Teppei Omori; Shinichi Nakamura; Katsutoshi Tokushige (Gastroenterology Research and Practice)
Objectives. The clinical/colonoscopic features of ulcerative colitis (UC) associated with primary sclerosing cholangitis (PSC), the prognostic impact of UC, and the utility of UC screening in PSC patients are unknown. We characterized UC associated with PSC and assessed UC’s impact on the prognosis of PSC and the importance of colonoscopic UC screening in PSC patients. Methods. We retrospectively analyzed the cases of 77 patients treated for PSC at a single center (April 2000–July 2019). We reviewed the clinical/colonoscopic profiles of the concurrent UC patients and compared the clinical profiles, survival, and primary causes of death between the patients with/without UC (n=35/n=42). The details of all patients’ colonoscopies were reviewed. Results. The concurrent UC group: 17 men, 18 women, diagnosed with PSC at the mean (SD) age of 36 (17) years; 21 patients (60%) had no UC symptoms. Colonoscopy revealed pancolitis in all patients, predominantly affecting the right-sided colon in 30 patients (86%). Lesions were scattered. Backwash ileitis (n=13, 37%) and rectal sparing (n=18, 51%) were observed. Most patients had mild UC; some had moderate or more severe UC (median Ulcerative Colitis Endoscopic Index of Severity (UCEIS) score 2; range, 1–5). Ludwig’s stage determined by liver biopsy did not correlate with the Mayo endoscopic score for UC. The patients with UC were diagnosed with PSC at a significantly younger age than those without UC (mean (SD), 36 [17] years vs. 55 [19] years, p<0.0001) and had a significantly higher 5-year survival rate (97.1% vs. 70.5%, p=0.0028). UC was detected in 19 of 34 asymptomatic patients (56%) who underwent colonoscopy screening. Conclusions. Our cohort’s clinical/colonoscopic features of UC associated with PSC are more moderate or severe UC than previous cases. The coexistence of UC might affect the prognosis of PSC. In this regard, colonoscopy in PSC patients is an important examination for determining prognosis. There is also asymptomatic UC in patients with PSC. In this regard, screening for colonoscopy in PSC patients is essential. When a diagnosis of PSC is made, immediate colonoscopy is a priority with UC complications in mind.